Is foreign language taught early or late in Indonesia? - Fitriah, Noor; Amrullah, M. Kholis; Arlentriadi, David (LPPM UIN Sulthan Thaha Saifuddin Jambi, 2022)
Curriculum 2013 (K-13) changes the structure of basic education where children should be emphasized more on teaching about the religious values ​​and culture of the state before they were exposed to foreign language. So, English is not compulsory subject that is taught in elementary school. Some literatures on second language learning recommends many factors that influence the success of learning language such as learning style, personality, motivation, and age. The age factor in learning foreign language is still becoming topic of debate, whether English is learnt early or late. In Indonesia, in the level of elementary school, English is taught as local content and not every elementary school choose English for that subject. Responding that issue this study mainly discussed about how age factor support learning English as foreign language. This study is critical analysis relevant books and journals. This conveyed that the age factor influence the foreign learning. Children are able to learn English before they turn to 12 years old, that stage language skills are developed. The teachers need to pay attention to the special young learners’ characteristic and optimally build the input comprehension of learners. And the English learning and teaching process should use also appropriate methods and techniques to create the real life environment. And Indonesia government should revitalize curriculum and facilitate the learning and teaching process, especially for foreign language.